The Effect of Spirit at Work and Compensation toward Employee Performance in PT. Arista Auto Lestari Medan - Pribadi, Teddi; Effendi, Ihsan; Suryani, Wan (Budapest International Research and Critics University, 2020)
The purpose of this study was to determine the